2012
DOI: 10.1097/tp.0b013e3182708e56
|View full text |Cite
|
Sign up to set email alerts
|

Is Cytomegalovirus Prophylaxis Dispensable in Patients Receiving an mTOR Inhibitor–Based Immunosuppression? A Systematic Review and Meta-Analysis

Abstract: mTOR-inhibitor treatment either alone or in combination with CNIs reduces significantly the CMV incidence after organ transplantation. With the use of an mTOR-inhibitor, CMV prophylaxis may be dispensible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 63 publications
7
85
2
4
Order By: Relevance
“…In contrast, the use of mammalian target of rapamycin (mTOR) inhibitors was more common among pediatric patients. A large amount of evidence supports the antiviral role of mTOR inhibitors, particularly in terms of a decreased risk for CMV infection (30,31), although this protective effect might have been diluted by the concomitant use of tacrolimus and the higher prevalence of CMVseronegative recipients (i.e. at risk of posttransplant primary infection) in the pediatric cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the use of mammalian target of rapamycin (mTOR) inhibitors was more common among pediatric patients. A large amount of evidence supports the antiviral role of mTOR inhibitors, particularly in terms of a decreased risk for CMV infection (30,31), although this protective effect might have been diluted by the concomitant use of tacrolimus and the higher prevalence of CMVseronegative recipients (i.e. at risk of posttransplant primary infection) in the pediatric cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic immune suppression in transplant recipients with mTORC1 inhibitors has significantly reduced the incidence of HCMV reactivation (44,45), implying an antiviral role of targeting mTORC1 in clinical settings. Moorman et al discovered that the HCMV protein pUL38 interacts with TSC2 and activates mTORC1 by antagonizing TSC function (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and meta-analysis have shown that the use of mammalian target of rapamycin inhibitors (mTORI, sirolimus, and everolimus), either de novo (13)(14)(15) or as a conversion strategy (16), are associated with lower rates of CMV infection. In all these trials, the population and management of CMV infection were largely heterogeneous with low representation of patients receiving no prophylaxis, who would benefit the most, primarily in transplant centers where CMV prophylaxis is not available or reimbursed.…”
Section: Introductionmentioning
confidence: 99%